MACULAR COLOBOMA - IN A CHILD WITH USHER SYNDROME - Ishaq, Mazhar; Mukhtar, Ahsan; Khan, Saim (Journal of Ayub Medical College Abbottabad, 2015)
Macular coloboma is a rare entity and its concomitance with Usher syndrome is described here. A 14 years male child was studied in detail along with other family members. He underwent two complete ophthalmologic examinations (4-years follow-up), including visual assessment, orthoptic evaluation, colour vision test, visual fields, corneal topography, Optical coherence tomography, fluorescein angiography, and electroretinography. Detailed ophthalmic examination was also conducted on other asymptomatic members of the same family. Patient had sensorineural deafness, poor visual acuity, and progressive visual field impairment in both eyes, bilaterally presenting macular coloboma and atypical retinitis pigmentosa pattern. The other investigated relatives did not show any specific and/or significant ocular disorder. This concurrence represents no genetic pattern and is observed in sporadic cases. Keywords: Retinitis pigmentosa, Usher syndrome, Macular coloboma